1997
DOI: 10.1159/000177992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Malnutrition and Atherosclerosis on the Fatty Acid Composition of Plasma Phospholipids in the Elderly

Abstract: The fatty acid profiles of plasma phospholipids have been compared in 53 elderly subjects suffering from malnutrition (group U, 17 subjects) or from atherosclerosis (group A, 15 subjects). A control group was also included in the study (group C, 21 subjects). Main differences were observed in phosphatidylcholine (PC). In group U, the proportion of monounsaturated fatty acids increased in PC, which was reflected by an increase in unsaturated fatty acids without significant modification of essential fatty acids.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The palmitic and palmitoleic acids were significantly high and low stearic was found in HBV-cirrhosis patients. Alvaro et al [ 43 ] found that an impaired FA elongation in cirrhosis may be due to augmented activity of Δ-9 desaturase and decreased the activity of elongase resulted in the decrease level of stearic acid and increased level of palmitoleic acid in cirrhosis patients [ 44 , 45 ]. The low level of linoleic acid increases the activity of Δ-9 desaturase [ 46 ], in addition, increased levels of palmitoleic and oleic acid with the FA status usually characterized by low linoleic acid [ 47 ] as observed in malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…The palmitic and palmitoleic acids were significantly high and low stearic was found in HBV-cirrhosis patients. Alvaro et al [ 43 ] found that an impaired FA elongation in cirrhosis may be due to augmented activity of Δ-9 desaturase and decreased the activity of elongase resulted in the decrease level of stearic acid and increased level of palmitoleic acid in cirrhosis patients [ 44 , 45 ]. The low level of linoleic acid increases the activity of Δ-9 desaturase [ 46 ], in addition, increased levels of palmitoleic and oleic acid with the FA status usually characterized by low linoleic acid [ 47 ] as observed in malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…(42,50) This process is even more exerted in the malnourished patients. Namely, low level of LA increased the activity of Δ-9 desaturase (51) increasing levels of palmitoleic and 18:1 n -9, with the FA status usually characterised by low LA n -6 (50,52) as observed in malnutrition.…”
Section: Discussionmentioning
confidence: 99%